I am not understanding this question.
I am not understanding this question. - 1

Answers

Answer 1
Answer:

Answer:

boardgamegeek.com/boardgame/245655/kings-dilemma

Step-by-step explanation:


Related Questions

Frans Summer job pays $200 per week. The circle graph shows how she spends the $200.50%savings10%movies15%other10%books15%clothingHow many dollars of Fran's weekly pay is spent on books and clothing?OA. $25OC. $50O D. $100OB. $30
Abigail invested $29,000 in an account paying an interest rate of 2.1% compoundedcontinuously. Assuming no deposits or withdrawals are made, how much money, tothe nearest dollar, would be in the account after 8 years?
What is the equation for this graph? Use y=mx+b
Four friends want to share two largepizzas equally. Each pizza is cut into ten slices. How many slices will each person get?
-3 < 5 true or false

The zeroes of the function are:
A) -2 and 0
B) 0 and 4
C) -2, 0, and 4

Answers

It would be C because they are the ones that función in , I think not sure

Which is bigger 0.159 or 1.590​

Answers

Answer:

1.590

Step-by-step explanation:

Answer:

0.159

Step-by-step explanation:its obvious hope this helped tho

Evaluate the expression when a=-5 and y=7.

Answers

Step by step explanation:

_______________________________

Step 1:

- 4a + y

Write the equation

_______________________________

Step 2:

=  - 4 * ( - 5) + 7

Insert the values of a ie -5 and y ie 7

_______________________________

Step 3:

= + 20 + 7

Multiply- 4 with -5 to get 20

_______________________________

Step 4:

= 27

add 20 with 7 to get 27

_______________________________

Final answer: 27

hope it helped you:)

Answer:

27

Step-by-step explanation:

We are given that a = -5 and y = 7 and we are asked to evaluate the expression -4a + y.

To evaluate the expression, we would plug -5 for a and 7 for y into the expression.

-4a + y = -4(-5) + 7 = 20 + 7 = 27

So -4a + y = 27.

I hope you find my answer and explanation to be helpful. Happy studying. :)

Which of the following is a RATE?12 to 3


12 stickers to 3 students

Answers

Answer:

gfgfcvfvghcghccghcgcvchdcfgcfcfrtyc

Step-by-step explanation:

PLEASE HELP!!!!!
will mark brainliest!!!!!

Answers

Answer:

fx =1; then fx =2; then fx =4

Step-by-step explanation:

then plug the coordinates in as x is horizontal bar in top right then the fx

Pleeease open the image and hellllp me

Answers

1. Rewrite the expression in terms of logarithms:

y=x^x=e^(\ln x^x)=e^(x\ln x)

Then differentiate with the chain rule (I'll use prime notation to save space; that is, the derivative of y is denoted y' )

y'=e^(x\ln x)(x\ln x)'=x^x(x\ln x)'

y'=x^x(x'\ln x+x(\ln x)')

y'=x^x\left(\ln x+\frac xx\right)

y'=x^x(\ln x+1)

2. Chain rule:

y=\ln(\csc(3x))

y'=\frac1{\csc(3x)}(\csc(3x))'

y'=\sin(3x)\left(-\cot^2(3x)(3x)'\right)

y'=-3\sin(3x)\cot^2(3x)

Since \cot x=(\cos x)/(\sin x), we can cancel one factor of sine:

y'=-3(\cos^2(3x))/(\sin(3x))=-3\cos(3x)\cot(3x)

3. Chain rule:

y=e^{e^(\sin x)}

y'=e^{e^(\sin x)}\left(e^(\sin x)\right)'

y'=e^{e^(\sin x)}e^(\sin x)(\sin x)'

y'=e^{e^(\sin x)+\sin x}\cos x

4. If you're like me and don't remember the rule for differentiating logarithms of bases not equal to e, you can use the change-of-base formula first:

\log_2x=(\ln x)/(\ln2)

Then

(\log_2x)'=\left((\ln x)/(\ln 2)\right)'=\frac1{\ln 2}

So we have

y=\cos^2(\log_2x)

y'=2\cos(\log_2x)\left(\cos(\log_2x)\right)'

y'=2\cos(\log_2x)(-\sin(\log_2x))(\log_2x)'

y'=-\frac2{\ln2}\cos(\log_2x)\sin(\log_2x)

and we can use the double angle identity and logarithm properties to condense this result:

y'=-\frac1{\ln2}\sin(2\log_2x)=-\frac1{\ln2}\sin(\log_2x^2)

5. Differentiate both sides:

\left(x^2-y^2+\sin x\,e^y+\ln y\,x\right)'=0'

2x-2yy'+\cos x\,e^y+\sin x\,e^yy'+\frac{xy'}y+\ln y=0

-\left(2y-\sin x\,e^y-\frac xy\right)y'=-\left(2x+\cos x\,e^y+\ln y\right)

y'=(2x+\cos x\,e^y\ln y)/(2y-\sin x\,e^y-\frac xy)

y'=(2xy+\cos x\,ye^y\ln y)/(2y^2-\sin x\,ye^y-x)

6. Same as with (5):

\left(\sin(x^2+\tan y)+e^(x^3\sec y)+2x-y+2\right)'=0'

\cos(x^2+\tan y)(x^2+\tan y)'+e^(x^3\sec y)(x^3\sec y)'+2-y'=0

\cos(x^2+\tan y)(2x+\sec^2y y')+e^(x^3\sec y)(3x^2\sec y+x^3\sec y\tan y\,y')+2-y'=0

\cos(x^2+\tan y)(2x+\sec^2y y')+e^(x^3\sec y)(3x^2\sec y+x^3\sec y\tan y\,y')+2-y'=0

\left(\cos(x^2+\tan y)\sec^2y+x^3\sec y\tan y\,e^(x^3\sec y)-1\right)y'=-\left(2x\cos(x^2+\tan y)+3x^2\sec y\,e^(x^3\sec y)+2\right)

y'=-(2x\cos(x^2+\tan y)+3x^2\sec y\,e^(x^3\sec y)+2)/(\cos(x^2+\tan y)\sec^2y+x^3\sec y\tan y\,e^(x^3\sec y)-1)

7. Looks like

y=x^2-e^(2x)

Compute the second derivative:

y'=2x-2e^(2x)

y''=2-4e^(2x)

Set this equal to 0 and solve for x :

2-4e^(2x)=0

4e^(2x)=2

e^(2x)=\frac12

2x=\ln\frac12=-\ln2

x=-\frac{\ln2}2